Design and deployment of the STEEER-AF trial to evaluate and improve guideline adherence: a cluster-randomized trial by the European Society of Cardiology and European Heart Rhythm Association - Sterliński, M; Bunting, KV; Boriani, G; Boveda, S; Guasch, E; Mont, L; Rajappan, K; Sommer, P; Mehta, S; Sun, Y; Gale, CP; van Deutekom, C; et al. (Oxford University Press, 2024)
Aims: The aim is to describe the rationale, design, delivery, and baseline characteristics of the Stroke prevention and rhythm control Treatment: Evaluation of an Educational programme of the European society of cardiology in a cluster-Randomized trial in patients with Atrial Fibrillation (STEEER-AF) trial. Methods and results: STEEER-AF is a pragmatic trial designed to objectively and robustly determine whether guidelines are adhered to in routine practice and evaluate a targeted educational programme for healthcare professionals. Seventy centres were randomized in six countries (France, Germany, Italy, Poland, Spain, and UK; 2022–23). The STEEER-AF centres recruited 1732 patients with a diagnosis of atrial fibrillation (AF), with a mean age of 68.9 years (SD 11.7), CHA2DS2-VASc score of 3.2 (SD 1.8), and 647 (37%) women. Eight hundred and forty-three patients (49%) were in AF at enrolment and 760 (44%) in sinus rhythm. Oral anticoagulant therapy was prescribed in 1543 patients (89%), with the majority receiving direct oral anticoagulants (1378; 89%). Previous cardioversion, antiarrhythmic drug therapy, or ablation was recorded in 836 patients (48.3%). Five hundred fifty-one patients (31.8%) were currently receiving an antiarrhythmic drug, and 446 (25.8%) were scheduled to receive a future cardioversion or ablation. The educational programme engaged 195 healthcare professionals across centres randomized to the intervention group, consisting of bespoke interactive online learning and reinforcement activities, supported by national expert trainers. Conclusion: The STEEER-AF trial was successfully deployed across six European countries to investigate guideline adherence in real-world practice and evaluate if a structured educational programme for healthcare professionals can improve patient-level care. Clinical Trial Registration: Clinicaltrials.gov, NCT04396418.